Resettlement and reintegration: single mothers' reflections after homelessness - Tischler, Victoria (Routledge, 2008)
Previous research has identified that most families who become homeless are women with dependent children. Homeless families are reported to have a variety of complex needs however little is known about the experiences of families once they are re-housed. The aim of this study was to explore psychosocial issues related to the resettlement experiences of single mothers following a period of homelessness. Qualitative semi-structured interviews were used to gather data from twenty one women living in a UK Midlands city. Thematic analysis was used to draw conclusions from the data. Findings indicated that despite exposure to major stressors most women had begun the process of resettlement by improving their physical surroundings. Women had achieved personal growth as they had managed to escape violence, overcome homelessness, and create new opportunities for themselves and their children. Suggestions are made for future research and improvements to services which would promote resettlement in this population.